Malaysian Administrative Law: A Review Of The Post-Uem Developments - Gan, Ching Chuan (Journal of Malaysian and Comparative Law, 1999)
An attempt is made in this article to review the Malaysian Administrative Law with particular emphasis on the case law developments and their implications in the post-UEM era.